PENGARUH KOMPLEKSITAS TUGAS TERHADAP KUALITAS AUDIT - Aulia Dewi Gizta,; Ranat Mulia Pardede, (Juremi: Jurnal Riset Ekonomi, 2023)
The purpose of this study was to examine the effect of task complexity on quality. The population of this study is all auditors at Public Accounting Firms in the Riau Islands Province. The sample in this study used a saturated sampling technique, which allows researchers to collect data from the entire auditor population. The total number of respondents in this study was 52 auditors. The data collection method was carried out using a questionnaire method. The results of this research indicate that task complexity influences audit quality